2011
DOI: 10.3382/ps.2010-01144
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of global gene response to chronic heat exposure in broiler chickens (Gallus gallus) reveals new reactive genes

Abstract: The process of heat regulation is complex and the exact molecular mechanism is not fully understood. To investigate the global gene response to chronic heat exposure, a breast muscle cDNA library and a liver tissue cDNA library from Silkie fowl were constructed and analyzed in bioinformatics. A total of 8,935 nonredundant EST were identified from and used for gene expression analysis. Microarray assay revealed that in breast muscle of broiler chickens (Gallus gallus), 110 genes changed expression levels after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 34 publications
0
23
0
3
Order By: Relevance
“…Heat stress in broilers impairs performance, induces intestinal injury and decreases macrophage activity, thereby reducing immune responsiveness (Quinteiro-Filho et al, 2010). Li et al (2011) showed that heat stress in broilers results in changes in gene expression. They found that 110 genes changed in gene expression after three weeks of heat stress, revealing genetic pathways involved in heat tolerance.…”
Section: Geneticsmentioning
confidence: 99%
“…Heat stress in broilers impairs performance, induces intestinal injury and decreases macrophage activity, thereby reducing immune responsiveness (Quinteiro-Filho et al, 2010). Li et al (2011) showed that heat stress in broilers results in changes in gene expression. They found that 110 genes changed in gene expression after three weeks of heat stress, revealing genetic pathways involved in heat tolerance.…”
Section: Geneticsmentioning
confidence: 99%
“…Transcriptomic studies have previously been conducted in the liver (Li et al 2011), breast muscle (Li et al 2011), testis and hypothalamus (Sun et al 2015). technologies have been employed to obtain a comprehensive understanding of the changes in heat-exposed chickens.…”
Section: Introductionmentioning
confidence: 99%
“…technologies have been employed to obtain a comprehensive understanding of the changes in heat-exposed chickens. Transcriptomic studies have previously been conducted in the liver (Li et al 2011), breast muscle (Li et al 2011), testis and hypothalamus (Sun et al 2015). Proteomic studies have been previously conducted in the breast and thigh muscles (Napper et al 2015), testis (Wang et al 2014), and gut microbiota .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Fulop [24] indicated that during the acute phase response, increase synthesis of APPs in the liver is measured by an increased transcription of APPs mRNA and elevation of their serum concentrations. In a recent study by Li et al [25] using a breast muscle and a liver tissue cDNA library from Silkie fowl by measuring the global gene response to chronic heat stress, found a new heat-reactive genes such as mitogen-activated protein kinase that play a significant role in heat regulation.…”
Section: Introductionmentioning
confidence: 99%